Real Assessment of Maximum Oxygen Uptake as a Verification After an Incremental Test Versus Without a Test - Hebisz, Paulina; Jastrzębska, Agnieszka Danuta; Hebisz, Rafał (Frontiers in Physiology, 2021)
The study was conducted to compare peak oxygen uptake measured with the incremental graded test (VO2peak) and two tests to verify maximum oxygen uptake, performed 15 min after the incremental test (VO2peak1) and on a separate day (VO2peak2). The aim was to determine which of the verification tests is more accurate and, more generally, to validate the VO2max obtained in the incremental graded test on the cycle ergometer. The study involved 23 participants with varying levels of physical activity. Analysis of variance showed no statistically significant differences for repeated measurements (F=2.28, p=0.118, η2=0.12). Bland–Altman analysis revealed a small bias of the VO2peak1 results compared to the VO2peak (0.4 mL∙min-1∙kg-1) and VO2peak2 results compared to the VO2peak (-0.76 ml∙min-1∙kg-1). In isolated cases, it was observed that VO2peak1 and VO2peak2 differed by more than 5% from VO2peak. Considering the above, it can be stated that among young people, there are no statistically significant differences between the values of peak oxygen uptake measured in the following tests. However, in individual cases, the need to verify the maximum oxygen uptake is stated, but performing a second verification test on a separate day has no additional benefit.